Flight activity of Melipona asilvai Moure (Hymenoptera: Apidae) - B. A. Souza; C. A. L. Carvalho; R. M. O. Alves (Brazilian Journal of Biology)
Many stingless bee species are specific to their areas of occurrence. Even when adapted to their local climate and flora conditions, they are subject to modifications in the environment, directly influencing flight activity. The aim of this work is to obtain information about the flight activity of the stingless bee Melipona asilvai Moure, thus contributing to the knowledge of this species. The flow of bees entering and leaving the colony was evaluated, and the type of transported material was identified. This information was correlated with climatic data collected at the time of observations, performed between June 2002 and March 2003. It can be proved that temperature was the factor with the greatest influence on the external activity of this species, showing a significant positive correlation with the entry of bees into the colony and pollen collection. Mud collecting showed a significant positive correlation with a humidity increase. Flight activity began at a temperature of 21.0 °C and humidity of 84.5%, peaking at 27.4 °C and 60.6% RH, respectively.